Pengaruh Sistem Akuntansi Pemerintahan (SAP), Implementasi Sistem Keuangan Tingkat Instansi (SAKTI), Kompetensi SDM Melalui Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan di Lembaga Pemerintah ABC - Elwisam; Yulianti Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out the impacts of the Government Accounting System (Sistem Akuntansi Pemerintahan/SAP), Agency-Level Financial System Implementation (Implementasi Sistem Keuangan Tingkat Instansi/SAKTI), Human Resources Competencies) through the Internal Control System (Sistem Pengendalian Internal/SPI) on the Quality of Financial statements in governmental institutions. This study used a quantitative approach using a questionnaire to obtain its data source and Warppls 7.0 App. There were 100 respondents as samples of this study, comprising the financial managers in the Governmental Institution ABC. The results show that the Government Accounting System (SAP), Agency-Level Financial System Implementation (SAKTI) Implementation, Human Resource Competencies, and the Internal Control System (SPI) have positive and significant impacts on the quality of financial statements of Governmental Institution ABC. The Internal Control System can mediate the impacts of the Government Accounting System (SAP) and the Agency-Level Financial System (SAKTI) Implementation on the Quality of Financial Statements in Governmental Institution ABC. This study's Total Coefficient of Determination is 0,697% or 68,7 &. It means that the model can explain the Information in 68,7% of data. Meanwhile, the remaining is explained by other variables not included in the model.